Integrating transcriptome and metabolome analyses to characterize flower development in Salix variegata franch., a typical dioecious plant - Huan Zhang; Wenqiao Li; Xiao Zhang; Rui Pan; Mingwei Tang; Yang Peng; Yiyun Wang; Youwei Zuo; Zhe Zhang; Hongping Deng (Scientific Reports)
Abstract Salix variegata, a typical dioecious plant with high reproductive and adaptive ability, has important ecological and ornamental value. To understand the potential mechanisms and metabolite dynamics of male and female flowers development, the first comparative analysis of the transcriptome and metabolome of S. variegata was applied. As a result, 12,245 differentially expressed genes (DEGs) and 4,145 differently expressed metabolites (DEMs) were identified. Transcriptomic analysis showed that the male and female flowers development processes were related to phenylpropanoid and flavonoid biosynthesis. According to the metabolic profile, the main amino acids, flavonoids, phenylpropanoids, and their derivatives were accumulated during the development of male and female flowers of the S. variegata. Combined transcriptomic and metabolomic analyses indicated that the AUX/IAA, bHLH, MIKC, MYB, NAC, ERF and RLK transcription factors (TFs) and their associated key DEGs may mediate the metabolism of phenylpropanoids and flavonoids, which in turn regulate the development of male and female flowers in S. variegata. These results provide important insights to elucidate the development of male and female flowers of S. variegata at the molecular level. Our results will contribute to understanding the molecular and genetic mechanisms of male and female flower development in typical dioecious plants.